1990
DOI: 10.1038/ki.1990.64
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-induced polycystic kidney disease—A threshold trait

Abstract: Administration of hydrocortisone acetate (250 mg/kg) to newborn mice caused polycystic kidney disease (PKD) of varying proportions in each of 18 different inbred strains; none of the injected controls were affected. All kidneys were histologically examined and scored for degree of cyst formation using a semi-continuous (0 to 4+) grading scheme. Results suggested that this condition is a multifactorial threshold trait. For each strain, estimates of the mean and standard deviation of normally distributed liabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The similar distance of Ke 6 from mammalian 17␤HSD4 and bacterial 7␣HSD, the activity of androgens and estrogens in the kidney, and the evidence that steroid hormones are involved in cyst formation (11)(12)(13)(14)(15)(16)(17) suggested to us that Ke 6 could metabolize a steroid. This prompted us to examine Ke 6 for 17␤HSD activity as described next.…”
Section: Phylogenetic Analysis Shows Ke 6 Is Close To Mammalianmentioning
confidence: 99%
See 1 more Smart Citation
“…The similar distance of Ke 6 from mammalian 17␤HSD4 and bacterial 7␣HSD, the activity of androgens and estrogens in the kidney, and the evidence that steroid hormones are involved in cyst formation (11)(12)(13)(14)(15)(16)(17) suggested to us that Ke 6 could metabolize a steroid. This prompted us to examine Ke 6 for 17␤HSD activity as described next.…”
Section: Phylogenetic Analysis Shows Ke 6 Is Close To Mammalianmentioning
confidence: 99%
“…The involvement of a steroid dehydrogenase in renal cyst formation is particularly intriguing since previously several laboratories had demonstrated that the rodent kidney is extremely vulnerable to cyst formation in response to steroid administration at a critical time in development (11)(12)(13)(14)(15)(16)(17). Moreover, the cystogenic potential of glucocorticoids has been directly demonstrated in metanephric kidneys in organ culture by us (5) and others (18).…”
mentioning
confidence: 99%
“…Plausibly, this could be a mechanism for glucocorticoid maturation of renal structure and function, although this remains to be tested. Conversely, high glucocorticoid levels in the perinatal period cause renal cysts (450).…”
Section: Fetal Kidneymentioning
confidence: 99%
“…Neonatal mice appear to have a small window of time in which they are susceptible to exogenous forces (i.e. glucocorticoids) inducing the development of a cystic phenotype [39,40]. In slowly progressive PKD, glucocorticoid treatment inhibits the progression of PKD [41].…”
Section: Discussionmentioning
confidence: 99%